Usability of the PBL Model-Based Poetry Riddle Teaching Module in Elementary Schools - Gantina Gantina; Dede Tri Kurniawan; Yusuf Tri Herlambang; Yadi Suryadi; Yoga Prima Putra; Budi Hendrawan (CV. Ksatria Siliwangi, 2024)
Learning Indonesian in elementary schools has an important role in developing students' literacy skills, including the ability to understand and write various types of texts, such as poetry. Problem-Based Learning (PBL) is a relevant learning model to be applied in learning poetry riddles. This research aims to analyze the usability or usability of PBL-based teaching modules on poetry puzzle material in elementary schools. This research uses quantitative research, namely the survey method using a questionnaire. The research results show that the largest variable is directed by the Feedback variable (UB) with a gain of 73% and the lowest variable is directed by User Activity (AP) with a gain of 13%. A high feedback value indicates good convergent validity, while a low value indicates there is room for improvement or development on the variable.